2012
DOI: 10.1002/jpln.201100063
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐ecological evaluation of willows in a floodplain

Abstract: Willows (Salix spp.) were supposed to be suitable candidates for the phytoremediation of polluted floodplain soils, but it is unknown how willow growth alters concentrations and mobility of pollutants under the conditions of ongoing periodically flooding. Therefore, effects of willow cropping on total concentrations and mobility of As and heavy metals and soil microbial properties were determined after three and four growing seasons under willows in comparison to native grassland in a flood channel of a River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(45 reference statements)
2
6
0
Order By: Relevance
“…Namely, enhanced plant uptake is species-specific, but can also be a result of dynamic soil reactions affecting As biogeochemical behaviour, such as oxidation-reduction, sorption-desorption, precipitation/dissolution and volatilisation, which can contribute to As transformation and speciation in the rhizosphere soil in the riparian zone (Fitz and Wenzel 2002;Alloway 2013). This is confirmed by a comparison with other species growing in riparian habitats, such as Salix species (Zimmer et al 2012;Delplanque et al 2013;Pavlović et al 2016) and Populus alba L. (Madejón et al 2004), which accumulated lower amounts of As. At the same time, the levels of As measured in roots and leaves were similar to those for U. laevis from uncontaminated sites, obtained by Budzyńska et al (2017) and Mleczek et al (2017), also with a higher content in roots than in leaves.…”
Section: Pte Levels In Plantsupporting
confidence: 66%
See 1 more Smart Citation
“…Namely, enhanced plant uptake is species-specific, but can also be a result of dynamic soil reactions affecting As biogeochemical behaviour, such as oxidation-reduction, sorption-desorption, precipitation/dissolution and volatilisation, which can contribute to As transformation and speciation in the rhizosphere soil in the riparian zone (Fitz and Wenzel 2002;Alloway 2013). This is confirmed by a comparison with other species growing in riparian habitats, such as Salix species (Zimmer et al 2012;Delplanque et al 2013;Pavlović et al 2016) and Populus alba L. (Madejón et al 2004), which accumulated lower amounts of As. At the same time, the levels of As measured in roots and leaves were similar to those for U. laevis from uncontaminated sites, obtained by Budzyńska et al (2017) and Mleczek et al (2017), also with a higher content in roots than in leaves.…”
Section: Pte Levels In Plantsupporting
confidence: 66%
“…Normal Cd levels in plants are considered to be in the range of 0.05-0.2 mg kg −1 (Kabata-Pendias 2011; van der Ent et al 2013), while toxic levels are > 5 mg kg −1 (McBride 1994;Mrvić et al 2009;Kabata-Pendias 2011;Alloway 2013;van der Ent et al 2013). All the Cd levels measured in root and leaf samples were elevated compared to normal levels in plants, but lower in comparison to different Salix and Populus species, which can accumulate considerable amounts of Cd and Zn in their aboveground organs (Vervaeke et al 2003;Meers et al 2003Meers et al , 2005Madejón et al 2004;Bedell et al 2009;Zimmer et al 2012;Delplanque et al 2013;Pavlović et al 2016). Likewise, they were lower than in Ulmus carpinifolia Gled.…”
Section: Pte Levels In Plantmentioning
confidence: 79%
“…For the latter, clones can be grown for specific SRC purposes and then imported and planted at their final destination areas [12,15]. Moreover, it has been observed that the inclusion of native species in SRC plantations can increase the biodiversity and the supply of ecosystem services at regional scale [16][17][18], allowing an effective phytoremediation of metalcontaminated areas [19][20][21][22][23]. Hence, solutions exist to provide synergic ecological benefits to the main energy-oriented goal of the SRC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compared to annual systems grown on arable land, the management of perennial Salix stands in SRC leads to decreased mechanical disturbance of the soil and changed biochemical soil properties; along with changes in the abundance and diversity of soil organisms including mycorrhizal fungi ( Baum et al, 2009a ; Hrynkiewicz et al, 2010a ; Fransson et al, 2013 ; Toju et al, 2013a ; Goldmann et al, 2015 ). In addition, Salix genotype identity can significantly affect the soil enzyme activities at the same site ( Baum and Hrynkiewicz, 2006 ), and Salix stands grown in a floodplain revealed higher activities of the soil enzyme β-glucosidase compared to perennial grassland ( Zimmer et al, 2012 ). Changed soil enzyme activities are considered to be a direct expression of the soil community to metabolic requirements and available nutrients, and can therefore be used as indicators of soil functional diversity.…”
Section: Introductionmentioning
confidence: 99%